Adoption of improved potato varieties and its impact on household nutrition: Evidence from Emba Alaje Woreda, northern Ethiopia - Ebrahim, Mohammed (Bahir Dar University, 2019)
High population pressure and continuous decrease of the land holding size results in increase of food insecurity. To meet the increasing food demand of the growing population there is a need to intensify production practices. In this regard, improved potato varieties production plays a great role in improving the household’s food security, food consumption, and food diversity, and there-by contributing to nutrition security. This study analyzes the probability and use intensity of improved potato varieties adoption and, the effect of adoption on households’ nutrition security. The data was collected in 2018 at Emba Alaje woreda from a survey of 370 households (185 improved potato variety growers and 185 non-growers). Sampling weights were used to account the proportion of the sample compared to the whole population. Tobit model was used to analyze the factors affecting the probability and use intensity of improved potato varieties adoption. Both propensity score matching (PSM) and endogenous switching regression model (ESRM) were used to analyze the impacts of improved potato varieties on households’ nutrition using Food security scale, Food consumption score and Household dietary diversity score proxy variables. To control the possible selection problem invers mill’s ratio was included in the second stage equations. Size of own land, distance of the nearest plot, access to extension services, the existence of neighbor adopter, perception on the improved potato varieties’ maturity period and tuber yield potential were found as the main factors of adoption probability and use intensity of improved potato varieties. The PSM result indicated that, adoption of improved potato varieties increases the average food security scale, food consumption score and the dietary diversity score by 1.79, 6.6 and 0.8 points, respectively. Similarly, the ESRM result confirmed that, improved potato varieties adoption increases the average food security scale, food consumption and dietary diversity score by 2, 6.1 and 1.4 points, respectively. Thus, to improve the nutritional status of the farming households, government should give due emphasis for potato production and the extension service need to be strengthen.